Microwave probe sensing location for Venturi-based real-time multiphase flowmeter - Zhan, Mengke (2023)
Real-time in-line interpretation of liquid properties is important for multiphase flow measurements. Therefore, it would be desirable to have a sensor, such as a microwave sensor, which can continuously measure the salinity of a flow. In addition to salinity measurement, the microwave sensor can also measure water fraction, which is required for a multiphase flowmeter based on single-energy gamma-ray attenuation; however, choosing a suitable probe sensing location for a microwave salinity sensor in a multiphase flowmeter can be challenging, as the sensor needs to be located at near-wall liquid-rich region to accommodate a wide range of flow conditions. Currently, a microwave sensor is installed in the lower area of a horizontal blind-tee inlet spool of a multiphase flowmeter for salinity measurement. Integrating the microwave sensor into the vertically mounted multiphase flowmeter can reduce the flowmeter (carbon) footprint and manufacturing costs and can improve water-to-liquid ratio measurement due to faster local oil-water mixing. The associated challenge is that the sensor needs to be located at near-wall liquid-rich region to accommodate a wide range of flow conditions, including high gas-volume-fraction flows, where the near-wall liquid layer present in the vertical pipe is usually very thin. In this study, computational fluid dynamics modeling is used to evaluate the suitability of four different sensing locations along the vertical cross-section of a Venturi-based multiphase flowmeter based on near-wall liquid-richness. The results show that the Venturi inlet is the most suitable location for microwave sensor measurement, compared to the mid-convergence section, the mid-divergence section, and the Venturi outlet for a range of inlet liquid-volume-fractions. The findings have been validated by experimental microwave sensor measurements in a multiphase flow loop facility.